Activities of nurses managing patients with depression - Petravičienė, Zita; Bartašiūnienė, Vida; Lagūnienė, Rosita (Slauga. Mokslas ir praktika, 2020)
The effects of depression on human health and the role of the nurse in helping a person suffering from depression are not sufficiently investigated yet. Nurses working with people with depression must constantly assess their current psychological condition, identify and meet the needs of nursing, teach how to manage the tension that has arisen, and control the prescribed treatment. Nursing should be based on a holistic approach – to look at a person and his illness - depression as a whole, to apply nursing interventions, methods and techniques to achieve the optimum human condition and its maintenance. The study was conducted in September – November, 2018, 54 nurses from Utena County X institutions participated in it. The study showed that nurse co-operation with a patient with depression and medication prescribed by a doctor is the most appropriate way to remove the symptoms of depression. Most respondents are able to recognize the symptoms of depression and consider depressive disorders to be partially cured, and in conflict situations, nurses tend to seek patience, understanding and communication, and are able to manage the conflicts caused by patients with depression.